Efficient PCR Amplification Protocol of Nuclear Microsatellites for Exuviae-Derived DNA of Cicada, Yezoterpnosia nigricosta - Yumoto, Keisuke; Kanbe, Takashi; Saito, Yoko; Kaneko, Shingo; Tsuda, Yoshiaki (Frontiers in Insect Science, 2021)
Although insect exuviae-based genetics is challenging, it can be a valuable method for obtaining reliable DNA resources by non-invasive sampling. This approach is especially effective when the target species is endangered/endemic or when sampling the adult is difficult. One example is cicadas, which during molt leave their exoskeletons on tree trunks, making them easily collectable. While cicada exuviae-derived DNA has previously been employed for mitochondrial DNA sequencing, this study aimed to develop a reliable method for the PCR amplification of nuclear microsatellite loci from cicada exuviae derived DNA for application in molecular ecology, conservation and population genetics. Five different PCR amplification protocols were performed, and the fragment patterns compared with those obtained using DNA extracted from adult individuals. Moreover, the relationship between the freshness of the exuviae and genotyping success was evaluated. TaKaRa LA Taq provided the best performance in the PCR amplification of DNA isolated from cicada exuviae and the electropherogram showed a clear fragment pattern that was equivalent to that obtained from the DNA extracted from the adult individual. This result suggests that cicada exuviae-derived DNA can be amplified by PCR and that multiple independent loci of nuclear DNA microsatellite markers can be easily genotyped. This study demonstrates that fresh cicada exuviae provide high quality DNA, which can be used for microsatellite genotyping. The methods developed in this study are applicable not only for cicada but other insect species for which exuviae are available. Thus, this study can make a significant contribution to insect sciences.